Preparation of Structural Phase Diagram of Nd2Ni1-XCuxO4+δ As New Cathode Materials – Clarification of Existence of Miscibility Gap. (30th May 2017) - Wang, Chengkun; Soga, Haruki; Hayashi, Tomoki; Morise, Takahiko; Niwa, Eiki; Hashimoto, Takuya
Abstract : Structural phase diagram of Nd2 Ni1- x Cu x O4+ δ, expected as new cathode material for solid oxide fuel cells, was established. The single phase with K2 NiF4 -type crystal structure was obtained for the specimens with x ≤0.3. Single phase with crystal structure of T'-phase was obtained for Nd2 CuO4 . For the specimens with x between 0.4 and 0.9, phase separation into K2 NiF4 structure and T'-phase structure due to miscibility gap was observed. In the miscibility gap, Cu content, x, of both K2 NiF4 phase and T'-phase was constant and the compositional ratio of T'-phase linearly increased with increasing x . From high temperature X-ray diffraction measurements, it was revealed that the miscibility gap remained up to 1000 °C for the specimens with x between 0.4 and 0.9.